Edukasi Pemberian Terapi Kompres Hangat Payudara Terhadap Penurunan Nyeri Payudara Pada Ibu Nifas - Ladyvia, Fiyola; Haryono, Nathasia Elga; Sinaga, Sri Putriani (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Poor management of breast care can result in premature cessation of breastfeeding. The main reason for early cessation of breastfeeding is due to pain caused by breast milk dams. One indicator of a child's health is exclusive breastfeeding. In Indonesia, exclusive breastfeeding coverage increased from 69.62% in 2020 to 71.58% in 2021 and 72.04% in 2022. This community service aims to enhance community awareness regarding the efficacy of warm breast compresses as an alternative therapeutic approach for managing breast engorgement in postpartum mothers. This study utilized a quasi-experimental design with pre- and post-test assessments. The target population for this research consisted of postpartum mothers on the third postpartum day residing within the service area of the Garung Community Health Center, Wonosobo Regency in August-September 2024 who experienced breast milk dams with a total of 6 respondents using probability sampling techniques with simple random sampling. Researchers divided respondents into 2 groups. The Wilcoxon Test was employed for data analysis. The statistical test results using the Wilcoxon Test, postpartum mothers with warm compresses with p value= 0.000, can be concluded p < 0.05. This indicates a statistically significant effect of warm compresses in alleviating breast pain among postpartum mother.